The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1101/2023.02.08.527742
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Maturation of Nucleus Accumbens Synaptic Transmission Signals a Critical Period for the Rescue of Social Deficits in a Mouse Model of Autism Spectrum Disorder

Abstract: Social behavior emerges early in development, a time marked by the onset of neurodevelopmental disorders featuring social deficits, including autism spectrum disorder (ASD). Although deficits in social interaction and communication are at the core of the clinical diagnosis of ASD, very little is known about their neural correlates at the time of clinical onset of the disorder. The nucleus accumbens (NAc), a brain region extensively implicated in social behavior, undergoes synaptic, cellular and molecular alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 179 publications
0
2
0
Order By: Relevance
“…Taken together, these findings suggest that interfering with complement‐mediated microglial pruning might delay symptoms and the onset of schizophrenia. Furthermore, studies in mouse models of autism, which show deficit in both pruning and social behavior, report a sensitive period in the NAc for effective treatment of social deficit (Matthiesen et al., 2023). These data suggest that understanding the healthy and abnormal regulation of temporally bound C3‐mediated pruning at the synaptic level may be important to understand complex neurodevelopmental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these findings suggest that interfering with complement‐mediated microglial pruning might delay symptoms and the onset of schizophrenia. Furthermore, studies in mouse models of autism, which show deficit in both pruning and social behavior, report a sensitive period in the NAc for effective treatment of social deficit (Matthiesen et al., 2023). These data suggest that understanding the healthy and abnormal regulation of temporally bound C3‐mediated pruning at the synaptic level may be important to understand complex neurodevelopmental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…To identify a potential neural substrate for this change, we adapted a viral activity-dependent tagging strategy for developing rats, which showed that distinct neural ensembles are activated by the social-threat test in infants versus juveniles. Future work will be necessary to more fully characterize the neural mechanisms supporting this change across weaning, although targeting downstream, functionally-dissociated projections, such as LHb-VTA-NAc and LHb-VTA-mPFC, is a promising approach 120,121 .…”
Section: The Lateral Habenula Integrates Developmental and Contextual...mentioning
confidence: 99%